Optical design and multi‐length‐scale scanning spectro‐microscopy possibilities at the Nanoscopium beamline of Synchrotron Soleil. (26th June 2015) - Somogyi, Andrea; Medjoubi, Kadda; Baranton, Gil; Le Roux, Vincent; Ribbens, Marc; Polack, François; Philippot, Pascal; Samama, Jean‐Pierre
<x xml:space="preserve">Abstract</x> The Nanoscopium 155 m‐long beamline of Synchrotron Soleil is dedicated to scanning hard X‐ray nanoprobe techniques. Nanoscopium aims to reach ≤100 nm resolution in the 5–20 keV energy range for routine user experiments. The beamline design tackles the tight stability requirements of such a scanning nanoprobe by creating an overfilled secondary source, implementing all horizontally reflecting main beamline optics, applying high mechanical stability equipment and constructing a dedicated high‐stability building envelope. Multi‐technique scanning imaging and tomography including X‐ray fluorescence spectrometry and spectro‐microscopy, absorption, differential phase and dark‐field contrasts are implemented at the beamline in order to provide simultaneous information on the elemental distribution, speciation and sample morphology. This paper describes the optical concept and the first measured performance of the Nanoscopium beamline followed by the hierarchical length‐scale multi‐technique imaging experiments performed with dwell times down to 3 ms per pixel.